ITS Community Service Program as A Medium to Empower Community in Facing the Era of Industrial Revolution 4.0 - Hermanto Hermanto (Institut Teknologi Sepuluh Nopember, 2019)
As agents of change, students are required not only to have knowledge and expertise in their fields, but they must also be ready to be in the community to implement the knowledge and skills they have, help solve real problems faced by the community or provide knowledge and skills to the community so they can lead better life. To meet these goals, Institut Teknologi Sepuluh November (ITS) conducted community service program (KKN) for students to communities. In line with ITS students’ background, the themes of KKN were related with technology and its applications, so that the KKN activities in the community were also inseparable from the theme of technology and its application. Thus, KKN ITS is the right medium to help the community in facing the current era of the industrial revolution in which technology and its application serve as its core.